Range dynamics mediated by compensatory life stage responses to experimental climate manipulations - Oldfather, Meagan F.; Koontz, Michael J.; Doak, Daniel F.; Ackerly, David D.; Levine, Jonathan (Ecology letters, 2021)
The expectations of polar or upslope distributional shifts of species ranges in response to warming climate conditions have been recently questioned. Diverse responses of different life stages to changing temperature and moisture regimes may alter these predicted range dynamics. Furthermore, the climate driver(s) influencing demographic rates, and the contribution of each demographic rate to population growth rate (λ), may shift across a species range. We investigated these demographic effects by experimentally manipulating climate and measuring responses of λ in nine populations spanning the elevation range of an alpine plant (Ivesia lycopodioides). Populations exhibited stable growth rates (λ ~ 1) under naturally wet conditions and declining rates (λ < 1) under naturally dry conditions. However, opposing vital rate responses to experimental heating and watering lead to negligible or negative effects on population stability. These findings indicate that life stage–specific responses to changing climate can disrupt the current relationships between population stability and climate across species ranges. We investigated the effects of climate manipulations on population dynamics in nine populations spanning the range of an alpine plant. We find evidence for inverse responses of different life‐history transitions to the climate manipulations, leading to negligible or negative effects on population stability. Broadly, this work indicates that life stage–specific responses to changing climate can disrupt current relationships between population stability and climate across species ranges.